Detection of HIV-1 resistant to antiretroviral drugs among tomsk oblast population with newly diagnosed HIV-infection - D. P. Zyryanova; E. M. Astakhova; M. P. Gashnikova; T. N. Ismailova; E. F. Bocharov; A. S. Chernov; A. V. Totmenin; M. N. Gashnikova (Журнал инфектологии, 2020)
The purpose of this paper is to evaluate the spreading of HIV-1 resistant to antiretroviral drugs among Tomsk Oblast population with newly diagnosed HIV-infection.Materials and methods. It was collected 122 clinical samples of  peripheral blood of HIV-infected patients from Tomsk Oblast who did not take antiretroviral drugs. In HIV-1 isolated from clinical samples we studied nucleotide sequence of genome fragments encoding virus protease and reverse transcriptase. Complex analyses of epidemiologic data from patients and the presence in genome HIV-1 mutations associated with resistance development to protease inhibitors and virus reverse transcriptase were carried out.Results. Analysis of HIV-1 isolated from Tomsk Oblast naïve HIV-infected population made it possible to detect HIV-1 mutations associated with a decrease of virus sensitivity to antiretroviral drugs in 9,8% of cases. Among described mutations 50% were associated with resistance to virus protease inhibitors; 33,3% were resistance mutations to nonnuclease inhibitors of reverse transcriptase, and 16.7% were resistance mutations to nucleoside inhibitors of virus reverse transcriptase. Out of 9,8% of resistant viruses 7,3% of casesincluded mutations associated with the development of potentially low level of reduction of HIV-1 sensitivity to drugs. Main HIV-1 resistance mutations of high and average levels were registered only in 2,5% of genotyped HIV-1 isolated from people who inject drugs.Conclusion. Current study detected considerably low sampling rate of HIV-1 carrying mutations associated with resistance to antiretroviral drugs among Tomsk Oblast naïve HIV-infected population. It is believed to be caused by a relatively short period of extensive application of antiretroviral therapy in that territory. Analysis of epidemiologic data resulted in detection of factors negatively affecting prediction of further development of HIV-infection epidemic in the region including prevalence of risk behavior practice contributing to resistant HIV-1 transmission both among patients via heterosexual contacts and among people who inject drugs.